Efficient Algorithm for Ocean Wave Profile Simulation in Malaysian Waters - Idris, Ahmad; Sati Hammonangan Harahap, Indra; Osman Ali, Montassir (International Journal of Engineering and Technology, 2018)
This study presents an approach for ocean wave simulation in Malaysian waters by using the eigenfunctions of Prolate Spheroidal Wave Functions in which fewer number of independent random variables are used. It is an efficient approach that can allow the use of state of the art stochastic methods in the analysis and design of offshore structures. An algorithm was also developed for the simulation of the wave in a computer program in which sub-routines were provided to solve the equations and matrices involved. The wave profile for the environmental parameters of the Malaysian offshore locations was simulated and the results presented.Â Â